Metodología de cuadricóptero con control y estabilidad imu, usando aplicación en dispositivo móvil android (2018)
The exposed methodology is presented as a technology grouping for the development of a functional prototype type drone, which is controlled from an application for Android devices that makes its management and start-up more flexible. The conjugation of the wireless technology from a Smartphone to the model airplane and its referenced answers, locate the IMU (Inertia Measurement Unit) as an appropriate option for the definition of stability and control in the servomotors of the ailerons. The IMU uses the accelerometer and the gyroscope of the mobile device to send the control signals to a XBEE that communicates with an Arduino microcontroller, in charge of executing the PID control commands and in turn feeding the loops respectively. App-inventor as software for on-line use, it is versatile in its programming for the design of applications, it allows to capture the signals of the IMU in a simple way and with them the points of reference necessary for the control of the quadrocopters.